Psychological assistance at disaster in Bulgaria - contemporary policies for health risk management. (20th October 2021) - Dimitrova, D; Georgieva, E
Abstract: Issue: Health risk management (HRM) in Bulgaria is provided to citizens in emergencies, disasters, accidents and catastrophes (E&DAC). According to the legislation in the country, this is a part of the mandatory package of medical provision for the injured population (MPIP) and concerns any acute life-threatening condition (LTC). In the dynamically changing environment of E&DAC, a special form of health consequences among survivors are related to mental health (MeH). Description of the problem: In practice, any serious E&DAC has a direct or indirect psychological impact. It can manifest itself acutely or remotely over time, puts the victims in temporary or permanent disability and is followed by serious social effects. A strategy has been proposed for inclusion in the obligatory package of MPIP in case of significant E&DAC and primary psychological assistance (PPA) for every citizen who has survived. Results: In the country, PPАs to citizens for decades is an on-demand service provided mainly by the private sector. Within the BRC, a group has been formed to provide PPA with a modest resource capacity. The emotional citizens culture in the country is far from active demand for PPA in general and severely limited in resources and the MeH is not a priority. This system of public health care, based on withdrawal from the MeH, also exposes to increased risk of psycho-somatic and distress-provoked physical illnesses (PSDPPhI). Lessons: Carrying out timely PPA for those in need changes the range of adverse mental effects, reducing them. Provides a better adaptive response to reduced risk of PTSD and PSDPPhI. A volume of preventive measures organized in stages over time gives a greater chance to a larger number of victims. Key messages: The health of the nation is a complex program for controlling both the acute health problems at E&DAC and the protection of MeH. To provide modern sustainable policies for the implication of PPA in everyone who has seriously experienced E&DAC is resulted in good health practices.